OFW remittances and real effective exchange rates evidence from the Philippines 2000-2020 - Pascual, Mark Joseph M.; Seno, Samantha (Quezon City School of Economics, University of the Philippines Diliman, 2022)
Migrant remittances augment most of developing countries’ external funding contributing to their economic growth, including the Philippines. The consistently massive inflows each year have revealed their increasing importance to households and the macroeconomy; however, some studies have warned of their undesirable effects in the foreign exchange market. Specifically, an increase in remittances tends to increase the real exchange rate and encourage a real currency appreciation that negatively affects trade balance. This paper examines the impact of remittances on the real effective exchange rate (REER) index of the Philippines from 2000 to 2020, along with trade variables like exports, imports, and foreign direct investment (FDI) that traditionally influence the foreign exchange market. After a logarithmic transformation and using multiple linear regression, this paper empirically validates that remittances can independently cause an appreciation and overvaluation of the peso. However, this is canceled out by the effect of imports as it depreciates the peso by almost the same magnitude. The opposing effects of remittances and trade on the economy depend on their respective degrees of over/undervaluation of the currency.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Remittances -- Economic aspects -- Philippines; Exchange Rates -- Economic aspects -- Philippines